Post-Processing Magnetic Measurement Data of Accelerator Magnets by the Boundary Element Method - Di Rienzo, Luca; Cosmai, Alberto; Russenschuck, Stephan (IEEE transactions on magnetics, 2017)
This paper deals with the application of the boundary element method to the post-processing of magnetic measurement data in accelerator magnets. In this way, field mapping can be limited to the domain boundary and the quantities of interest, e.g., the magnetic flux density along a trajectory or multipole field errors, can be computed from the boundary data.